Successfully treatment of chronic hepatitis C with direct-acting antiviral agents: a single center experience - Kartal, Aysun; Turan Gökçe, Dilara; Gümüşsoy, Mesut; Örüncü, Mehmet Berk; Örmeci, Necati; Yurdaydın, Cihan; Özkan, Hasan; Idilman, Ramazan (Turkish Journal of Gastroenterology, 2019)
INTRODUCTION: The aim of the present study was to evaluate the efficacy and tolerability of ledipasvir/sofosbuvir (LDV/SOF) with or without ribavirin (RBV), and Ombitasvir- ritonavir/Paritaprevir/Dasabuvir (PrOD) with or without RBV in the treatment of chronic hepatitis C (CHC). METHODS: We evaluated consecutive 72 CHC patients who were treated with direct-acting agents (DAAs) in our clinic. Patients received LDV (90 mg) and SOF (400 mg) in a fixed-dose combination tablet once daily and PrOD regimen ± RBV for 12 or 24 weeks based on physicians’ discretion. The primary endpoint of the study was defined as the absence of quantifiable HCV-RNA levels in serum at 12 weeks after the end of the treatment (sustained virological response [SVR]). The secondary endpoints were defined as improvements in Child-Pugh score and MELD score, tolerability of the treatment (adverse events). Serum HCV-RNA levels were measured using the Roche (CA, USA) CobasAmpliPrep/Cobas TaqMan HCV Test, version 2.0. RESULTS: All patients were Caucasian, predominantly female gender (53%). The mean age was 62.6 years. Among them, 90% were infected with genotype 1b. The majority of the patients (85%) had previously received interferon-based antiviral treatment for HCV infection; 93% of them were non-responded. Approximately, more than half of the patients had cirrhosis (56%). The percentages of Child-Pugh class A, B, and C with cirrhosis were 50%, 38% and 12%, respectively. Median MELD score was 10. Four patients had liver transplantation. SVR12 was achieved in 100%. SVR was not different among patients with treatment-naïve and treatment-experience, in patients with/without cirrhosis and among patients with Child-Pugh Class A, B and C (p>0.05). From baseline to SVR12, serum ALT level (60±43U/L to 22±12 U/L, p=0.014 and MELD score (9.9±4.5 to 7.0 ±0.9) were significantly improved pCONCLUSION: A combination treatment of LDV/SOF or PrOD with or without R were an effective and tolerable treatment in CHC patients. HCV eradication is associated with improvements of liver function.